Stocking for a trophy bass fishery: searching for size differences among largemouth bass and hybrids in southern Arkansas reservoirs. (2nd April 2016) - Lamothe, Karl A.; Allen, Ryan M.; Winningham, Kelly; Dennis, Colton; Johnson, Ronald L.
ABSTRACT: Lamothe KA, Allen RM, Winningham K, Dennis C, Johnson RL. 2016. Stocking for a trophy bass fishery: searching for size differences among largemouth bass and hybrids in southern Arkansas reservoirs. Lake Reserve Manage. 32:194–207. Within the southern United States, game and fish agencies have introduced nonnative Florida bass (FB), Micropterus floridanus (Lesueur 1822), as an alternative to native northern largemouth bass (NLMB), M. salmoides (Lacèpéde 1802), for decades because of suspected maximum size differences between the 2 species. The goal of this study was to determine if bass with differing levels of FB alleles demonstrated differential size structure within 6 southern Arkansas reservoirs stocked with FB. Despite millions of FB being introduced into these reservoirs over the last decade, FB made up <2% of the sampled bass for 5 of 6 reservoirs. Most sampled populations consisted primarily of one species and hybrids genetically similar to that species. In Lake Monticello, where FB numbers were relatively high, FB had significantly greater mean lengths and weights than FB × NLMB hybrids. By contrast, other reservoir bass populations showed no significant pairwise differences among species or their hybrids. From a fisheries management perspective, introducing FB outside its native range remains a controversial issue, and long-term controlled studies are needed in Arkansas to better resolve size differences observed among FB, NLMB, and their hybrids.